2005
DOI: 10.1021/jp0511000
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Contributions to Indole−Lipid Interactions

Abstract: The role of electrostatic forces in indole-lipid interactions was studied by (1)H and (2)H NMR in ether- and ester-linked phospholipid bilayers with incorporated indole. Indole-ring-current-induced (1)H NMR chemical shifts of lipid resonances in bilayers of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, 1,2-dioleoyl-sn-glycero-3-phosphocholine, 1,2-di-O-octadecenyl-sn-glycero-3-phosphocholine, and 1,2-di-O-octadecenyl-sn-glycero-3-phosphomethanol show a bimodal indole distribution, with indole residing at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
97
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 38 publications
17
97
0
Order By: Relevance
“…Aromatics have both polar and hydrophobic characters and are known to favor the lipid-water interface location (33). Flanking aromatics confer resistance against displacement to experimental peptides embedded in bilayers (34,35). A survey of residue distribution shows interfacial preference for tryptophan, tyrosine, and histidine, although not for phenylalanine (36).…”
Section: Homologous Mutations In the Yeast Trpy1 And The Fly Trpc1 Havementioning
confidence: 99%
“…Aromatics have both polar and hydrophobic characters and are known to favor the lipid-water interface location (33). Flanking aromatics confer resistance against displacement to experimental peptides embedded in bilayers (34,35). A survey of residue distribution shows interfacial preference for tryptophan, tyrosine, and histidine, although not for phenylalanine (36).…”
Section: Homologous Mutations In the Yeast Trpy1 And The Fly Trpc1 Havementioning
confidence: 99%
“…A trace of approximately 30 s was analyzed for events greater than 1 ms (>200 events) at each holding potential using Clampfit 10.0 (pClamp 10.0). The mean current amplitudes of each seal were averaged, plotted and fitted to a linear equation using GraphPad Prims v. 4. The mean open time was determined by selecting open events using the half-amplitude criterion and plotting it in a histogram of the logarithm of open time using Clampfit 10.0.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Tryptophan and tyrosine tend to localize at the water-hydrocarbon core interface (WHc interface, also known as polar "head groups") near the carbonyl region of the membrane as has been demonstrated by molecular simulations of integral proteins, high-resolution structural studies of integral proteins, and NMR studies with tryptophan analogs. [4][5][6][7][8] Phenylalanine also tends to be localized at the WHc interface, but can also be accommodated within the hydrocarbon core. 1 Studies on small peptides, tryptophan-analog molecules and simulations studies, suggest that the tendency to be located at the WHc interface arises from a combination of intermolecular interactions and entropic effects associated with the rigid aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 NMR studies on indole derivatives embedded in lipid bilayers have 40 demonstrated that the dipole moment of the indole group, cation-π interactions and the ability of the indole group to participate in hydrogen bonding interactions with lipids all contribute to localisation in the interfacial region. 11,[14][15][16] More recently however, steric effects and dipole-dipole 45 contributions have been suggested to be more important than hydrogen bonding or cation-π interactions for determining the membrane partitioning and alignment of these and related indole derivatives. 10 Molecular dynamics simulations of mixed indole-lipid and tryptophan-lipid systems indicate a 50 preference for indole to localise at specific locations in relation to membranes, including the middle of the bilayer, proximal to the choline headgroup and in the region of the lipid carbonyl groups, with the latter being the preferred site.…”
Section: Introductionmentioning
confidence: 99%